2014
DOI: 10.1039/c3ra43644f
|View full text |Cite
|
Sign up to set email alerts
|

Generation of reactive aryl radical intermediates in the reductive photodehalogenation of itraconazole

Abstract: The photochemical properties of itraconazole (1), a broad-spectrum antifungal agent, have been investigated in connection with reported skin photosensitivity disorders. Steady state photolysis, fluorescence and phosphorescence experiments have been performed to understand photoreactivity of 1 in biological media. The drug is unstable under UVB irradiation, suffering a primary dehalogenation of the 2,4-dichlorophenyl moiety that occurs mainly at the ortho-position. In poorly H-donating solvents, such as acetoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 35 publications
3
24
0
Order By: Relevance
“…The structure of IP‐7 was assigned on the basis of the molecular ion obtained at m / z 669.3, which corresponds to the loss of HCl from the parent drug and was also described by Nardi et al . (). It is also worth noting that, contrary to the findings of Nardi et al ., we have detected new products (IP‐1 to IP‐3) which are a result of breakdown of the C–N bond.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…The structure of IP‐7 was assigned on the basis of the molecular ion obtained at m / z 669.3, which corresponds to the loss of HCl from the parent drug and was also described by Nardi et al . (). It is also worth noting that, contrary to the findings of Nardi et al ., we have detected new products (IP‐1 to IP‐3) which are a result of breakdown of the C–N bond.…”
Section: Resultsmentioning
confidence: 97%
“…Another two derivatives of ITZ without one chloride atom in the phenyl ring, one in the ortho (IP-6) and the second in the para position (IP-5), were previously described (Dettlaff et al, 2015). Dettlaff et al studied the ionizing radiation effects, in the form of an electron beam, on ITZ in the solid phase, and Nardi et al (2014) showed that ITZ is unstable under UV-B irradiation suffering from a primary dehalogenation of the 2,4-dichlorophenyl moiety. The structure of IP-7 was assigned on the basis of the molecular ion obtained at m/z 669.3, which corresponds to the loss of HCl from the parent drug and was also described by Nardi et al (2014).…”
Section: Photodegradation Of Itzmentioning
confidence: 99%
See 3 more Smart Citations